Fatherhood in Transition : Masculinity, Identity and Everyday Life - Johansson, Thomas; Andreasson, Jesper (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book discusses and analyses the ways in which fatherhood is in transition in contemporary and globalized society. The authors identify and examine fathering practices in relation to hegemonic and marginal patterns of masculinity, the concept of heteronormativity and sexuality, and patterns of segregation, class and national differences. Contextualised in relation to theories of fatherhood and relevant statistics, Fatherhood in Transition presents rich empirical material gathered in a number of western countries. It focuses on key themes including transnational fathering and families, gay fathers and the virtual global arena of fatherhood images found on the internet. Containing a number of new discussions about masculinity and fatherhood, whilst contributing to and developing existing debates and theories about men, masculinity, gender and society, this book will be of interest to students and scholars across a range of disciplines, including Men's Studies, Gender Studies, Sociology, Psychology, Media Studies and Cultural Studies.
Keywords: Social sciences.; Childhood.; Adolescence.; Social groups.; elektronické knihy; electronic books